Lanzamiento de Flying Tiger Copenhagen en el Perú - Aguilar Tomey, Diego Santiago (2022)
The purpose of this work is to devise a launch campaign for the Danish brand Flying Tiger Copenhagen in Peru. It is intended to position the brand as a retail that stands out for its variety of products, unique design, affordable price and environmental responsibility, attributes sought by the target audience, people between 27 and 45 years of socioeconomic level B and C who care about their well-being, always taking care of its economy and the environment. Throughout the report, an analysis of the economic and social situation of the country was carried out, as well as of the retail sector in order to build a solid proposal based on real data. The launch campaign will be presented, containing the communication strategy both online and offline, focused on the consumer and governed by a budget established according to the objectives.